Tonal Landscapes: Re-membering the interiority of lives of apartheid through the family album of the oppressed - O'Connell, Siona (African Studies, 2015)
This research seeks to be a methodological contribution to the fields of visual and memory studies. It enters these conversations through the family photograph found in the home of forcibly removed ex-residents of Roger Street, District Six, Cape Town in an attempt to think about ways of living during and after apartheid. Through this study, practically and theoretically, I engage with the challenges of restorative justice and contemplate how the family photograph may be engaged as a transactional object of translation in this contested area. I look at apartheid through District Six land claims and address as well, questions of trauma, memory, and freedom in the aftermath of apartheid. This dissertation therefore seeks to place three seemingly distinct literatures in the same frame: that of photography, that of memory, and that of justice and freedom. Conflicts over land, both local and global, range across the continuum, where long-term residents are displaced to make way for new developments and the other extreme where residents are forcibly displaced, violently evicted. What is clear in all of these instances, however, is that the problem cannot be reduced to one of monetary remuneration, that the land itself is imbued with meaning that cannot be measured in monetary terms. It is important to recognize - not only that land/place may mean different things to different people, but also that it can mean multiple "things" to the same person. Unless we recognize the multidimensionality of the meanings of land, as well thinking about what it means to be oppressed, any attempts to engage in restitution or restorative justice are destined to fail. This thesis attempts to think through how an ordinary object - the photograph - can be used to gain an interior look into how oppressed people lived during apartheid, and how they continue to live after its demise. Antjie Krog's book, Country of My Skull draws attention to the issue of death during apartheid. What this thesis does is to look at what happens to those who lived through apartheid and how they deal with the aftermath. It looks at the move from death to life. The family photograph may at first glance appear to have little in common with the issue of restorative justice. They both however speak of public and private, of remembering and mourning, of death and life, of absence and presence. They are both prone to multiple interpretations, as well as being at the cutting edge of contemporary and political debates. Taken together, the family photograph and visual studies form a forceful space, initiating interdisciplinary dialogue and providing a creative and scholarly engagement that has both local and global implications.